JURIDICAL ANALYSIS OF DEPOSIT GUARANTEE AGENCIES FOR BANKING COMPANIES LIQUIDATED - Utami, Nisri Atul (Inspiring Law Journal, 2024)
A bank is a financial institution that withdraws funds from the public which are then managed by the bank for other business needs and channeled back to the community in the form of loans. And not only that, in the current era banks have become financial institutions in the flow of payments, fees and levies related to the needs of the community related to their business with other people and/or with certain institutions. So with this very complex governance, banks must be able and trustworthy by the public to carry out their mandate with integrity and credibility. A person who saves funds and/or uses banking services in every business activity at a bank is due to the public's trust as customers in that bank who are believed to be able to play a role and help with banking problems as part of their life needs with the availability of various banking facilities at a bank. This research was conducted using a normative juridical approach. This research uses qualitative analysis techniques which are then explained and analyzed using descriptive analytical methods. The type of approach used in writing this thesis is a library research approach, namely by studying books and documents related to the title and problem formulation. This research also takes an approach using the statutory regulatory approach method, namely by reviewing statutory regulations related to the title and formulation of the problem used as discussion in this research. The results of the research and discussion in this study found that in carrying out the business operations of a bank, it really depends on the financial situation and conditions of the bank itself as a bank's resilience and strength in facing challenges and obstacles both globally and domestically. This can be seen from the global recession that occurred which resulted in a monetary crisis in Indonesia. Many banking institutions at that time were affected and experienced shocks in their business operations, went bankrupt, went bankrupt and were ultimately liquidated. This is the background to the establishment of the Deposit Insurance Corporation (LPS), which was initiated by the government to help banking institutions and protect their customers. With the provisions of the law and mechanisms that have been established. This is done by the government so that people continue to trust banks in managing public finances